Daylight control and performance in office buildings using a novel ceramic louvre system. (15th March 2019) - Urbano Gutiérrez, R.; Du, J.; Ferreira, N.; Ferrero, A.; Sharples, S.
Abstract: This study examined the design and daylight performance of a new louvre screen for office buildings. The screen was evaluated for three different material finishes: specular aluminium as a traditional material commonly used in louvres, and two types of ceramic finishes, with the intention to reduce the systems' environmental impact. The new system was assessed taking an unshaded window, a window with a rod screen and a window with venetian blinds as references. Annual performance simulations for a full-scale room, using the lighting software Daysim, were conducted to assess the effect of the three material systems on indoor daylighting levels and distributions using both the traditional Daylight Factor and climate-based daylighting metrics (Daylight Autonomy DA and Useful Daylight Illuminance UDI). The results show that the proposed louvre system can provide satisfactory daylight levels and visual comfort within the room, while ceramics appear as a promising alternative material to be used in the production of advanced daylighting technologies. Highlights: New louvre profile outperforms current standard profile for daylighting in buildings. Ceramics shows a very positive performance as a material for daylighting technology. Ceramic new louvre offers improved ecological impact and daylighting performance.